Information Management in Public Communication in The City Governments of Banda Aceh and Langsa - Barlian Erliadi; Harapan Tua; Firman Firman; Rafika Duri (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2026)
Information management in public communication has become an important issue in local government administration because citizens increasingly rely on official digital channels to obtain accurate, transparent, and timely public information. This study examines information management in public communication within the City Governments of Banda Aceh and Langsa, focusing on the use of official websites as strategic instruments for disseminating public information, strengthening transparency, and supporting communication between government and citizens. The objective of this study is to compare how Banda Aceh and Langsa manage public information through their official digital platforms and to identify the institutional factors that influence differences in website utilization and communication effectiveness. This study employed a qualitative approach with a comparative descriptive design. Data were collected through website observation, documentation study, and institutional information tracing by examining official website features, news updates, public information menus, service integration, and supporting organizational capacity. The data were analyzed using qualitative descriptive analysis through data reduction, data presentation, comparative interpretation, and conclusion drawing. The findings show that both city governments have official websites and similar institutional responsibilities in managing public information; however, their communication performance differs significantly. Banda Aceh demonstrates a more active and integrated model of digital public communication, supported by competent internal staff and approximately twenty external personnel who assist in activating agency websites and updating public news. Its website provides broader features, including public information services, open data, media center, command center, and digital service links. In contrast, Langsa has established an official website with several information menus, but its utilization as a strategic public communication platform remains less optimal.